Using Transcranial Direct Current Stimulation to Enhance Creative Cognition: Interactions between Task, Polarity, and Stimulation Site - Weinberger, Adam B.; Green, Adam E.; Chrysikou, Evangelia G. (Frontiers in Human Neuroscience, 2017)
Creative cognition is frequently described as involving two primary processes, idea generation and idea selection. A growing body of research has used transcranial direct current stimulation (tDCS) to examine the neural mechanisms implicated in each of these processes. This literature has yielded a diverse set of findings that vary depending on the location and type (anodal, cathodal, or both) of electrical stimulation employed, as well as the task’s reliance on idea generation or idea selection. As a result, understanding the interactions between stimulation site, polarity and task demands is required to evaluate the potential of tDCS to enhance creative performance. Here, we review tDCS designs that have elicited reliable and dissociable enhancements for creative cognition. Cathodal stimulation over the left inferior frontotemporal cortex has been associated with improvements on tasks that rely primarily on idea generation, whereas anodal tDCS over left dorsolateral prefrontal cortex (DLPFC) and frontopolar cortex has been shown to augment performance on tasks that impose high demands on creative idea selection. These results highlight the functional selectivity of tDCS for different components of creative thinking and confirm the dissociable contributions of left dorsal and inferior lateral frontotemporal cortex for different creativity tasks. We discuss promising avenues for future research that can advance our understanding of the effectiveness of tDCS as a method to enhance creative cognition.